THE EFFECTIVENESS OF DUOLINGO IMPLEMENTATION TO IMPROVE STUDENTS' VOCABULARY MASTERY - Berlian, Liska (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2025)
This research aims to examine the effectiveness of Duolingo to improve students' vocabulary mastery among junior high school students grade 8 at MTs Bustanul Aulad. Pre-experimental approach was used in this research with one group pretest-posttest before and after the use of Duolingo application. Questionnaire is also used to explore students' perspectives regarding their experiences. The participant of this research were 10 students of class 8 in Mts Bustanul Aulad. Results showed a significant improvement in vocabulary acquisition, with the mean posttest score rising from 53 to 85.5, as well as a T-test result of 0.0006 which was less than 0.05. Students also expressed positive perceptions towards the use of Duolingo, which was considered fun, interesting and useful for vocabulary development. The results of this research indicate that Duolingo is an effective language game-based application to improve vocabulary acquisition among students.